Terapi AIUEO terhadap Kemampuan Berbicara (Afasia Motorik) pada Pasien Stroke - Ni Made Dwi Yunica Astriani; Putu Indah Sintya Dewi; Mochamad Heri; Ni Kadek Erika Widiari (Journal of Telenursing (JOTING), 2019)
The purpose of this study is to analyze the effect of aiueo therapy on speech (motor aphasia) in stroke patients at Kertha Usada General Hospital. The research design used in this study is pre experimental with one group pre post test design. The results of the study obtained the results of the average value of pre 3.61 and the average value of post 5.21. The test results using the Paired t-test obtained p (0,000) <α (0.05). Conclusion, there is an influence of AIUEO therapy on speech (motor aphasia) in stroke patients at Kertha Usada General Hospital. Keywords: Speech Ability, AIUEO Therapy